A Small Ku-Band Polarization Tracking Active Phased Array for Mobile Satellite Communications. (6th November 2013) - Shi, Wei; Qian, Zuping; Zhou, Jun; Qu, Xinbo; Xiang, Yang; Hong, Liu
Abstract : A compact polarization tracking active phased array for Ku-band mobile satellite signal reception is presented. In contrast with conventional mechanically tracking antennas, the approach presented here meets the requirements of beam tracking and polarization tracking simultaneously without any servo components. The two-layer stacked square patch fed by two probes is used as antenna element. The impedance bandwidth of 16% for the element covers the operating frequency range from 12.25 GHz to 12.75 GHz. In the presence of mutual coupling, the dimensional parameters for each element of the small 7 × 7 array are optimized during beam scanning and polarization tracking. The compact polarization tracking modules based on the low-temperature cofired ceramic (LTCC) system-in-package (SiP) technology are proposed. A small active phased array prototype with the size of 120 mm (length) × 120 mm (width) × 55 mm (height) is developed. The measured polarization tracking patterns of the prototype are given. The polarization tracking beam can be steered in the elevation up to 50°. The gain of no less than 16.0 dBi and the aperture efficiency of more than 50% are obtained. The measured and simulated polarization tracking patterns agreed well.